Wear in diesel injection systems, the effect of the high sulfur content in diesel oil 2 - Valderrama, Andrés (2009)
The fuel used in thermal machines and equipment used in the various productive activities of the transport sectors, mining, energy, others are 2 diesel oil, which due to their high levels of sulfur and burning run, it produces sulfur dioxide (SO2) and sulfate particles, so it is difficult to reduce air pollution generated by the use of petroleum diesel 2, without removing the sulfur in its formulation, and prevents the use of many conventional and advanced technologies for the control of pollutants, including Carbon monoxide (CO), particulate matter (PM) nitrogen oxides (NOx) and hydrocarbons (HC) In this work, we verified experimentally the impact of the use of diesel oil 2, which has high sulfur content in its formulation, the components of diesel injection system of the turbocharged diesel engine with electronically controlled Caterpillar 3412, HEUI model, is performed micrometric measurement of wear of the nozzle of the injector and injector push rod is displayed traces of erosion and pitting of the valve seats and injector poppets.